ARTIFICIAL INTELLIGENCE AS A LEARNING MEDIA IN ENGLISH EDUCATION: BIBLIOMETRIC USING BIBLIOSHINY ANALYSIS (2009-2023) - Zafrullah, Zafrullah; Meisya, Adinda; Ayuni, Rizki Tika (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2024)
This research examines the publication trends and emerging keywords within the domain of artificial intelligence applied to English education. Analyzing 74 documents sourced from Scopus using RStudio and Vosviewer revealed distinct patterns. Notably, the year 2021 marked a significant milestone with 26 articles, constituting 35.14% of total publications, while the preceding decade (2009-2020) contributed only 13 articles, representing less than 18%. However, the period from 2021 to 2023 experienced a noteworthy surge, introducing over 80% of the total publications, incorporating 60 new articles. Esteemed institutions like Hebei University of Engineering in China and three other affiliates each contributed 4 publications. The prominence of the ACM International Conference Proceedings Series underscores the influential role of technology conferences in shaping discussions around artificial intelligence in English education. An influential article, cited 20 times, focused on the integration of 5G and AI technologies to reform English education at universities, considering the necessity of cutting-edge technological infrastructure. Visual analysis highlights specific keywords such as speech recognition, quality control, teaching systems, and learning algorithms within yellow circles, suggesting potential areas for further research in the intersection of artificial intelligence and English education.